OxInflammatory response in wound healing and using Commiphora leptophloeos leaves and barks to control the OxInflammation - Lopes, Fernanda Barbosa (2024)
Inflammation is the body's response to tissue damage and is characterized by a series of events involving different cell types with the ability to secrete chemical mediators that are key to tissue repair processes. To compile a book, we carried out a literature review and noted that the main cells involved in inflammatory responses are neutrophils, macrophages and other cells of the immune system. The first step in the inflammatory response is the upregulation of genes such as nuclear factor kappa ß (NFK-ß) and the activation of a multi-protein complex known as the inflammasome, which serves as a platform for the activation of caspase-1, which cleaves pro-IL-1-ß and pro-IL-18 into activated interleukin-1 (IL-1ß) and interleukin-18 (IL-18). The secretion of these mediators results in the recruitment of leukocytes, which rapidly produce reactive oxygen and nitrogen species that increase vascular activation and the phagocytic capacity of cells to remove dead cells and debris. In this sense, oxidative stress emerges as a critical link between inflammation and tissue repair, affecting cell migration and consequently the process of tissue repair resolution. Thus, inappropriate activation of the NLRP3 inflammasome can trigger chronic inflammation and tissue damage, establishing a vicious cycle between ROS and the persistence of the inflammatory process (OxInflammation). Understanding these mechanisms is therefore essential for the development of effective therapeutic approaches to promote effective and infection-free tissue repair. Based on this, this study provides a mechanistic theory to explain the process of OxInflammation during tissue repair by analyzing the methodological quality of current evidence. It also attempts to understand how exposure to plant extracts from Commiphora leptophloeos can control the process of Oxyinflammation in macrophages. Therefore, a systematic review was conducted according to the PRISMA guidelines, with a structured search of MEDLINE (PubMed), Scopus and Web of Science databases, and 23 original studies were analysed. Bias analysis and study quality were assessed using the SYRCLE tool. The results showed activation of membrane receptors such as IFN-d, TNF-a and toll-like receptors in phagocytes, especially macrophages, during the initial phase of skin wound repair. In addition, positively regulated pathways such as STAT1, IP3 and NF-kß were identified, as well as Ca2+ mobilization associated with ROS production and activation of the inflammasome pathway (NLRP3). The proteolytic consequences of caspase-1 are the cleavage and release of the now active IL-1ß and IL-18, which play roles in immune modulation and vasodilation. These findings are important for understanding the mechanisms involved in skin tissue repair and for developing effective therapeutic approaches. In the second study, the plant Commiphora leptophloeos, known as 'Imburana', showed antioxidant and anti-inflammatory properties by negatively regulating the process of OxInflammation, possibly due to the presence of quinic acid tannins and oligomeric B-type procyanidins in the stem bark and the presence of six flavonoid C-glycosides (orientin, isoorientin, vitexin, isovitexin, isoquercitrin and quercetrin) in its leaves. Our results showed =80% inhibition of the free radical DPPH, increased cell viability and protection against protein denaturation, hemolysis, as well as a reduction in ON and H2O2 levels and an increase in the cell migration index for both parts of the plant. Commiphora leptophloeos extracts showed efficacy in reducing oxidative inflammation, as evidenced by a decrease in the expression of TLR4 and NF-?ß, leading to a decrease in the pro-inflammatory cytokines BAX, IL-6, TNF-a and COX2. At the same time, there was an increase in the expression of NFR2, which helps to control oxidative stress and resolve acute inflammation. However, the expression of HO-1 and HIF-1 decreased, suggesting a cross- regulation between NF-?ß, HO-1 and HIF-1. The results suggest that condensed tannins at stem bark concentrations (50 and 100µl) showed therapeutic potential in vitro by reducing OxInflammation and restoring cellular homeostasis, probably due to the action of condensed tannins, thereby demonstrating their efficacy in vitro. Due to its high concentration of flavonoid C-glycosides, the leaf extract has been shown to possess potent antioxidant properties with cosmetic potential, offering protection against premature aging and damage induced by free radicals, UV rays and pollution. These findings highlight the need for further studies to better elucidate the underlying mechanisms of action. Keywords: inflammation; oxidative stress; oxInflammation; cytokines; wound healing; imburana; Commiphora leptophloeos.